Distinguishing the Roles of Antibiotic Stewardship and Reductions in Outpatient Visits in Generating a 5-Year Decline in Antibiotic Prescribing. (16th March 2020) - Kissler, Stephen M; Klevens, R Monina; Barnett, Michael L; Grad, Yonatan H
Abstract: Background: The mechanisms driving the recent decline in outpatient antibiotic prescribing are unknown. We estimated the extent to which reductions in the number of antibiotic prescriptions filled per outpatient visit (stewardship) and reductions in the monthly rate of outpatient visits (observed disease) for infectious disease conditions each contributed to the decline in outpatient antibiotic prescribing in Massachusetts between 2011 and 2015. Methods: Outpatient medical and pharmacy claims from the Massachusetts All-Payer Claims Database were used to estimate rates of antibiotic prescribing and outpatient visits for 20 medical conditions and their contributions to the overall decline in antibiotic prescribing. Trends were compared with those in the National Ambulatory Medical Care Survey (NAMCS). Results: Between 2011 and 2015, the January and July antibiotic-prescribing rates per 1000 individuals in Massachusetts declined by 18.9% and 13.6%, respectively. The monthly rate of outpatient visits per 1000 individuals in Massachusetts declined ( P  < .05) for respiratory infections and urinary tract infections. Nationally, outpatient visits for antibiotic-meriting medical conditions also declined between 2010 and 2015. Of the estimated 358 antibiotic prescriptions per 1000 individuals averted over the study period in Massachusetts, 59% (95% CI, 54–63%) were attributable to reduced observed disease and 41% (95% CI, 37–46%) to improved stewardship. Conclusions: The decline in antibiotic prescribing in Massachusetts was driven both by a decline in observed disease and improved antibiotic stewardship, in agreement with national trends. A focus on infectious disease prevention should be considered alongside antibiotic stewardship as a means to reduce antibiotic prescribing. Abstract : In an observational analysis of insurance claims from Massachusetts, a 17% decline in antibiotic prescribing was attributed primarily to reductions in outpatient visits and secondarily to improved stewardship. Preventing the need for outpatient visits could substantially reduce antibiotic prescribing.